Analisis Pelayanan E-Government dalam Pembuatan Akta Kelahiran pada Dinas Kependudukan dan Pencatatan Sipil di Kecamatan Kandis Kabupaten Siak - Vitrah Damayanti; Beby Mashito Batubara; Evi Yunita Kurniati (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2022)
This study aims to find out how the service of the Population and Civil Registration Service of Siak Regency in making Birth Certificates. To find out what are the obstacles in making a Birth Certificate during the process change from manual to using an electronic-based signature. This research is a qualitative research. The research used is descriptive qualitative research. This research focuses intensively on one particular object which is studied as a case. Based on the results of research on the services of the Population and Civil Registration Service of Siak Regency in implementing the issuance of electronic signature-based birth certificates, there are several obstacles in the birth certificate making service, namely the disruption of network connections from the center which results in delays in the data input process and not a few of the public do not received a lot of information about the change in making birth certificates from manual to Electronic Sign -based. This shows that the Disdukcapil of Siak Regency has not provided maximum service regarding changes in making Electronic Sign based birth certificates but the Disdukcapil of Siak Regency is trying to provide the best service to create good government.